Homeostatic plasticity shapes the visual system’s first synapse - Robert E. Johnson (Nature Portfolio, 2017)
Retinal rod bipolar cells (RBCs) partially undergo programmed cell death triggering cell density-dependent plasticity. This study shows that increased removal of RBCs using genetic approaches causes dendrites of the remaining RBCs to expand and contact more rod photoreceptors while reducing connectivity with each.